A critical analysis of the Literature on Motivation: Exploring the Dimensions and Effects of Motivational Strategies (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Over the past two decades, academic institutions and major corporations have invested instudies of motivation. The authors of this research have conducted a comprehensive literature analysis toidentify all facets of motivation that may have an indirect or direct impact on motivational strategies.Employee happiness and the quality of work output are thought to have benefited by the use of the variousmotivating approaches outlined in this research, but the model needs to be confirmed via quantitativeassessments. This article reviewed the literature on motivation and proposed a theoretical frameworkthat takes into account its many dimensions.Large amounts of research, mostly from a variety ofperiodicals, have been merged to explore the numerous concerns brought up in this work relating toemployee motivation. Only papers published in the recent two decades were considered in order to keepthe study as up-to-date as possible. Existing academic literature only uses a small subset of motivation'smany aspects to describe the many models of motivation theory and their effects on workers' motivation.A key innovation of this research is its theoretical underpinnings the authors have attempted to developa construct with aspects that have direct or indirect effects on workers' motivation.